2021
DOI: 10.52628/87.2.22
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the relationship between trochlear morphology and medial patellar cartilage defect using magnetic resonance imaging

Abstract: The aim of this study was to evaluate trochlear morphology in patients with medial patellar cartilage defects via magnetic resonance imaging (MRI). Three hundred patients who were diagnosed with grade 2, 3 and 4 medial patellar cartilage defect using MRI according to the International Cartilage Repair Society Classification System and 100 control subjects were evaluated. Trochlear morphology was evaluated based on lateral trochlear inclination (LTI), medial trochlear inclination (MTI), sulcus angle( SA), femo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
1
1
Order By: Relevance
“…The rate of trochlear facet asymmetry was lower and that of patellar facet asymmetry was higher in patients with chondromalacia than in those without chondromalacia. However, in a recent study, contrary to our results, no relationship was found between trochlear facet asymmetry and patellar cartilage defect (16). Moreover, in a study by Resorlu et al, no relationship was found between patellar facet asymmetry and chondromalacia patella (17).…”
Section: Discussioncontrasting
confidence: 99%
“…The rate of trochlear facet asymmetry was lower and that of patellar facet asymmetry was higher in patients with chondromalacia than in those without chondromalacia. However, in a recent study, contrary to our results, no relationship was found between trochlear facet asymmetry and patellar cartilage defect (16). Moreover, in a study by Resorlu et al, no relationship was found between patellar facet asymmetry and chondromalacia patella (17).…”
Section: Discussioncontrasting
confidence: 99%
“…In order to proportionally reveal the morphological differences occurring in the patellofemoral joint, ratios such as pML/SA, SD/LCL, MFC‐LFC/LFL, mFL/LFL and ID/LCL were also calculated 23–25 . The study employed two distinct analytical approaches to examine the relationship between arthropathy severity and measured variables.…”
Section: Methodsmentioning
confidence: 99%
“…Patellofemoral (PF) joint incongruency, lower extremity axial malalignment, and abnormal mechanical or functional characteristics of the surrounding muscles and ligaments of the PF joint are some of the predisposing etiological features that the researchers have focused on. [ 3 - 5 ] The muscles and ligaments of the patella primarily provide stability and secondarily allow a concerted motion in the trochlear groove. By drawing it medially, superiorly, and posteriorly, the vastus medialis muscle and its distal part, the vastus medialis obliquus (VMO) muscle, stabilize the patella against the vastus lateralis (VL) muscle.…”
Section: Introductionmentioning
confidence: 99%